Body water space and turnover rate in female Katjang X Jamnapari goats. - Tuen, A.A.; Alimon, A.R.; Jelan, Z.A. (1984)
In order to obtain some based-line data on body water space and turnover rate in goats in Malaysia, tritiated water dilution technique was used to measure these two parameters in five pregnant and five non-pregnant does ( > 1 year) as well as in five young (+ 5.4 month-old) female goats. The young goats has a significantly (P <0.05) hinger body water space (898 ml.kg live weight) than either the pregnant (827 ml/kg liveweight) or non-pregnant (848 mi/kg live weight) does, respectively. Body water space (Y, litre) was strongly and positivelt related to live weight (X,kg) : Y = 0.629 + 0.805 X, r = 0.997 ; P < 0.001. The mean turnover rate and half-lives of body water did not differ significantly between the groups; the mean values for all animals were 124.5 m1/kg/d and 4.9 days for water furnover rate and half-lives, respectively. These values were discussed in relation to their future use in the measurement of feed and mineral supplement intake by grazing goats.